Acute Intermittent Porphyria Associated with Respiratory Failure: A Multidisciplinary Approach - Mayra Gonçalves Menegueti; Alkmim-Teixeira Gil Cezar; Karin Aparecida Casarini; Kátia Simone Muniz Cordeiro; Anibal Basile-Filho; Olindo Assis Martins-Filho; Maria Auxiliadora-Martins (Critical Care Research and Practice)
Despite being challenging, delivery of effective nursing care to patients with acute intermittent porphyria is a matter of utmost importance. In this paper, the diversity of symptoms and the difficult diagnosis of this condition are emphasized, and details concerning the treatment of this disorder in the intensive care unit are presented. We believe that acute intermittent porphyria should be borne in mind during performance of differential diagnosis of neurological, psychiatric, and gastroenterological disorders on patients whose routine investigation tests are normal, especially when precipitating factors exist. Intensive care measures and a multidisciplinary team approach are essential.